2020
DOI: 10.12659/ajcr.922830
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intestinal Infarction Due to Diffuse Jejunoileal and Mesenteric Lipomatosis in a 39-Year-Old Woman

Abstract: Unusual clinical course Background:Although lipomas are common benign tumors of adipose tissue, diffuse lipomas involving the small bowel, large bowel, and mesentery are rare. Multiple non-encapsulated lipomas characterize diffuse intestinal and mesenteric lipomatosis. Intestinal lipomatosis can be asymptomatic or may result in complications such as intussusception, volvulus, intestinal obstruction, or hemorrhage due to mucosal ulceration. A rare case is presented of intestinal infarction due to diffuse segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The pathophysiology of intestinal lipomatosis remains unknown but may be related to dysregulation of adipose metabolism, ectopic adipose deposition during embryogenesis, chemotherapy, or as part of genetic syndromes. 10,15 Our patient's incidental finding of incomplete intestinal malrotation may support a disruption in embryogenesis as a potential etiology. FLNA gene mutations, and PTEN hamartoma syndromes, including Cowden syndrome have been associated with intestinal lipomatosis, 16 yet despite extensive testing, no known genetic predisposition was identified in this patient.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The pathophysiology of intestinal lipomatosis remains unknown but may be related to dysregulation of adipose metabolism, ectopic adipose deposition during embryogenesis, chemotherapy, or as part of genetic syndromes. 10,15 Our patient's incidental finding of incomplete intestinal malrotation may support a disruption in embryogenesis as a potential etiology. FLNA gene mutations, and PTEN hamartoma syndromes, including Cowden syndrome have been associated with intestinal lipomatosis, 16 yet despite extensive testing, no known genetic predisposition was identified in this patient.…”
Section: Discussionmentioning
confidence: 70%
“…Case reports from across the globe have previously associated small intestinal lipomatosis with various causes of intestinal obstruction, diverticulosis, intestinal bleeding, intestinal infarction, malabsorption, and small intestinal bacterial overgrowth (SIBO). [4][5][6][7][8][9][10][11][12] Here, we present the case of a man with diffuse jejunal lipomatosis and chronicle his disease progression with multiple complications.…”
Section: Introductionmentioning
confidence: 99%
“…The patient of Kumar et al [ 10 ] had been ill for 5 days with severe vomiting symptoms, and CT showed ileal lipoma leading to slight bowel torsion, compared with our case (the present case) in which diffuse infiltrative small bowel lipomatosis involved the jejunum ileum more extensively and was surrounded by exudates, and more emphasis was placed on analyzing the CT manifestations. Previous reports in the literature on clinical symptoms in patients with diffuse infiltrative small bowel lipomatosis are scarce, but Cojocari et al [ 9 ] report that the patient came to the clinic with 12 h of abdominal pain, nausea, vomiting, and absence of bowel symptoms and that intestinal lipomatosis had already been diagnosed in the past. The patient had multiple lipomas in the intestines and mesentery, presented with small bowel infarcts, and had a habit of frequent bowel movements postoperatively, which were special features, and no slight bowel torsion occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The site of location, the number and the size of lipomas in the intraperitoneal cavity are largely different and present with a variety of symptoms without specificity. According to the site, they are mesenteric, antimesenteric and submucosa lipoma while for the number, isolated lipoma, multiple circumscribed lipomas, diffuse nodular lipomatosis, and diffuse adipose tissue infiltration of the submucosa without tumor formation are described in literature [5] .…”
Section: Discussionmentioning
confidence: 99%